Effect of Piperine on Antihyperglycemic Activity and Pharmacokinetic Profile of Nateglinide - Sama, V.; Nadipelli, M.; Yenumula, P.; Bommineni, M. R.; Mullangi, R. (Arzneimittelforschung, 2012)
Piperine (CAS no: 94-62-2), an alkaloid obtained from Piper nigrum and P. longum is a known inhibitor of various enzymes (CYP isozymes) responsible for biotransformation of drugs. By inhibiting the metabolism of drugs, piperine improves the bioavailability of drugs. In the present study piperine (10 mg/kg) significantly increased the dose-dependent anti-hyperglycemic activity of nateglinide (CAS no: 105816-04-4) as evaluated by glucose challenged and alloxan-induced diabetic models, when it was administered with nateglinide. Nateglinide plasma concentrations were also increased, when administered with piperine. The synergistic anti-hyperglycemic activity of nateglinide when administered with piperine can be attributed to increased plasma concentration of nateglinide. The results of this study demonstrate that piperine could be used as a potential bioenhancer along with nateglinide.
Keywords: piperine; nateglinide; antihyperglycemic; rats; pharmacokinetics